Theoretical study of the adsorption of BMSF-BENZ drug for osteoporosis disease treatment on Al-doped carbon nanotubes (Al-CNT) as a drug delivery vehicle - Al-Sawaff, Zaid Husham; Dalgic, Serap Senturk; Kandemirli, Fatma (European Journal of Chemistry, 2021)
The adsorption energy of the BMSF-BENZ adsorbed complexes was investigated to understand the non-local dispersion interactions, with many other chemical parameters related to this subject like HOMO and LUMO, energy gap, and the time needed for the BMSF-BENZ to be desorbed from the nanotube (recovery time). Our study reveals that Al-CNT is a promising adsorbent for this drug as Eads of BMSF-BENZ/Al-CNT complexes are -22.09, -38.68, -12.89, -31.01, -27.31, -21.90, and -21.42 kcal/mol in the gas phase on the active atoms of the BMSF BENZ (Br, N8, N9, N58, O35, O41, and S), respectively. In addition, the spontaneous and favorable interaction between the BMSF BENZ and all nanoparticles was confirmed by investigating Gibbs free energy and quantum theory of atoms in molecule analysis (QTAIM) so that it can be used as an electrochemical sensor or biosensor. Furthermore, to more visualize the nature of intermolecular bonding and the strength of interaction between the BMSF-BENZ drug molecule and the nanotube, QTAIM has been widely studied in the case of drug delivery purposes.  Al-CNT (4,0) can be extended as a drug delivery system and the work function type sensor.
Keywords: 3. Good health